Film, film with release film, molded article, and acoustic transducer

By adding organic particles to the silica resin composition to adjust their types and content, the problems of peeling difficulties and film deformation after shaping of the vibration plate are solved, and the effects of high shape retention, shapeability and low elasticity are achieved, and the working rate and shape stability are improved.

JP2025046022APending Publication Date: 2025-04-02MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023154156
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

The existing vibration plates have difficulty in peeling off after forming, low working rate, thin filming, poor quality, and low shape stability.

Method used

By adjusting the type and content of organic particles, the viscoelastic properties of film are improved so that they have good shape retention and shape preservation before forming, and maintain a low elasticity after forming, preventing the type and content of organic particles.

Benefits of technology

It realizes high shape retention and shape preservation before forming, and prevents the shape after forming, improves the working rate and shape stability of film, and is suitable for the vibration plate of small electrical audio converters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025046022000003
    Figure 2025046022000003
  • Figure 2025046022000004
    Figure 2025046022000004
  • Figure 2025046022000005
    Figure 2025046022000005
Patent Text Reader

Abstract

To provide a film that maintains excellent handleability in the uncrosslinked state, exhibits excellent thermal formability, and preserves a low elastic modulus even after curing.SOLUTION: A film comprises a resin composition including a silicone resin and organic particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film, a film with a release film, a molded article, and an acoustic transducer. [Background technology]

[0002] The widespread use of small electronic devices such as smartphones, PDAs, notebook computers, DVDs, LCD TVs, digital cameras, and portable music devices has led to an increased demand for small speakers (usually called micro-speakers) and small receivers used in these electronic devices, as well as small electro-acoustic transducers such as microphones and earphones. Polyetherimide (PEI) resin, polyether ether ketone (PEEK) resin, and other resins are widely used for the diaphragms used in these electro-acoustic transducers.

[0003] In recent years, the use of silicone resin in the above-mentioned diaphragm has also been considered. For example, Patent Document 1 discloses a sheet for diaphragms, which is formed by sequentially laminating a release sheet, a first layer made of an uncured liquid silicone composition, and a second layer mainly containing thermoplastic polyurethane, and a method for manufacturing a diaphragm using this sheet for diaphragms. In Patent Document 1, the sheet for diaphragms is set in a mold and shaped, and then the release sheet is peeled off from the molded product to manufacture a diaphragm. The sheet for diaphragms described in Patent Document 1 uses an uncured liquid silicone composition, so that it can improve the shaping property during molding and can also improve the conformability to the mold.

[0004] Furthermore, Patent Document 2 discloses a photocurable silicone gel composition that has stable vibration absorption properties even after long-term storage and contains a polyorganosiloxane having a (meth)acrylic group at its end, silicone powder, a photoinitiator, and silica treated with an alkylsilane compound having 10 or more carbon atoms (Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-152817 A [Patent Document 2] International Publication No. 2014 / 061390 Summary of the Invention [Problem to be solved by the invention]

[0006] The diaphragm sheet proposed in Patent Document 1 is made of an uncured liquid silicone composition, and is set in a mold to be shaped. Therefore, it is necessary to peel off the release film after molding, but the heat and pressure applied during molding often make it difficult to peel off the release film from the first layer, which reduces work efficiency and causes problems when mass-producing. Therefore, it is desirable to remove the release film from the diaphragm sheet before setting it in a mold such as a metal mold, but without the release film, the first layer made of the uncured liquid silicone composition will stick to the mold, causing problems such as making it difficult to remove the molded product from the mold. Furthermore, without the release film, the diaphragm sheet of Patent Document 1 will have poor shape retention before shaping. In order to solve the above problems, the present inventors have proposed a single-layer silicone film that is curable and has a static friction coefficient of 3 or less on at least one side (Patent Application No. 2022-102919). By using this silicone film, it is possible to provide a silicone film that can prevent the film from sticking to a mold during molding while improving shape retention before molding and shapeability during molding.

[0007] In recent years, devices have tended to become smaller, and there is a demand for thinner films. This has given rise to new problems. That is, when a silicone film is made thinner, for example, when it is made thinner than 100 μm, the film loses its stiffness and handling becomes poor. Specifically, the film breaks during handling, wrinkles, and other problems occur in shape stability. To improve handling, there is a method of increasing the stiffness of the silicone film by selecting a silicone resin with high hardness and taking measures such as increasing the degree of crosslinking to increase the degree of hardening at the time of semi-hardening. However, increasing the stiffness of the silicone film in this way reduces its thermal formability and makes it difficult to handle, i.e., it becomes difficult to adjust the balance between the degree of hardening and formability of the film.

[0008] Furthermore, in order to increase the stiffness of silicone, it is effective to incorporate particles; for example, the above-mentioned Patent Document 2 discloses the addition of silicone powder and silica treated with an alkylsilane compound having 10 or more carbon atoms to a silicone gel composition. However, although compounding with inorganic particles as disclosed in Patent Document 2 can increase the stiffness of the silicone film, the elastic modulus of the film after curing becomes too high, deteriorating the acoustic characteristics of the diaphragm, such as the sound quality and reproducibility.

[0009] Therefore, an object of the present invention is to provide a film which has excellent heat formability while maintaining good handleability before crosslinking, and which can maintain a low elastic modulus even after curing. [Means for solving the problem]

[0010] As a result of extensive investigations, the present inventors have found that the above problems can be solved by blending organic particles with a silicone resin, and have completed the present invention as described below. That is, the present invention provides the following.

[0011] [1] A film made of a resin composition containing a silicone resin and organic particles. [2] The film according to [1] above, wherein the content of the organic particles is 5 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the silicone resin. [3] The film according to [1] or [2] above, wherein the organic particles are at least one selected from the group consisting of silicone rubber powder, silicone resin powder, silicone composite powder, crosslinked acrylic particles, and crosslinked urethane particles. [4] The film according to any one of the above [1] to [3], which has thermosetting properties. [5] The film according to any one of the above [1] to [4], having a gel fraction of 30 to 95%. [6] The film according to any one of the above [1] to [5], which, upon thermal curing, exhibits the following viscoelastic properties (a) to (c): (a) Storage modulus E' at a measurement temperature of 25°C and a frequency of 10 Hz 25 is between 0.1MPa and 5MPa. (b) Storage modulus E' at a measurement temperature of 200°C and a frequency of 10 Hz 200 is between 0.1MPa and 5MPa. (c) Storage modulus E' 25 Storage modulus E' 200 The ratio (E' 200 / E' 25 ) is between 0.2 and 1.5. [7] The film according to any one of the above [1] to [6], which is for use in acoustic components. [8] A film with a release film comprising the film according to any one of the above [1] to [7] and a release film on at least one side of the film. [9] A molded article comprising a resin composition containing a silicone resin and organic particles, and having the following viscoelastic properties (a) to (c): (a) Storage modulus E' at a measurement temperature of 25°C and a frequency of 10 Hz 25 is between 0.1MPa and 5MPa. (b) Storage modulus E' at a measurement temperature of 200°C and a frequency of 10 Hz 200 is between 0.1MPa and 5MPa. (c) Storage modulus E'25 Storage modulus E' 200 The ratio (E' 200 / E' 25 ) is between 0.2 and 1.5.

[10] The molded article according to [9] above, wherein the content of the organic particles is 5 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the silicone resin.

[11] The molded article according to [9] or

[10] above, wherein the organic particles are at least one selected from the group consisting of silicone rubber powder, silicone resin powder, silicone composite powder, crosslinked acrylic particles, and crosslinked urethane particles.

[12] The molded article according to any one of the above [9] to

[11] , which is for an acoustic component.

[13] An acoustic transducer comprising the molded article according to any one of the above items [9] to

[12] . Effect of the Invention

[0012] According to the present invention, it is possible to provide a film which has excellent heat formability while maintaining good handleability before crosslinking, and which can maintain a low elastic modulus even after curing. [Brief description of the drawings]

[0013] [Figure 1] 1 is a cross-sectional view showing the structure of a micro-speaker diaphragm 1 according to one embodiment of the present invention. [Diagram 2] 10 is a cross-sectional view showing the structure of a micro-speaker diaphragm 11 according to another embodiment of the present invention. [Diagram 3] 11 is a plan view showing the structure of a micro-speaker diaphragm 21 according to another embodiment of the present invention. FIG.

[0014] Hereinafter, an embodiment of the present invention (hereinafter, sometimes referred to as "the present embodiment") will be described in detail. However, the following description is an example of an embodiment, and the present invention is not limited to this in any way.

[0015] [film] The film of the present invention (hereinafter sometimes referred to as "the present film") is characterized by being made of a resin composition containing a silicone resin and organic particles. Furthermore, the molded article of the present invention (hereinafter sometimes referred to as "the molded article") is made of a resin composition containing a silicone resin and organic particles, and is characterized by having the following viscoelastic properties (a) to (c). (a) Storage modulus E' at a measurement temperature of 25°C and a frequency of 10 Hz 25 is 0.1MPa or more and 5MPa or less (b) Storage modulus E' at a measurement temperature of 200°C and a frequency of 10 Hz 200 is 0.1MPa or more and 5MPa or less (c) Storage modulus E' 25 Storage modulus E' 200 The ratio (E' 200 / E' 25 ) is between 0.2 and 1.5 Each of the constituent elements will be described in detail below.

[0016] [Resin composition] The resin composition according to the present invention (hereinafter sometimes referred to as "the present resin composition") contains a silicone resin and organic particles. By including organic particles, the film has an appropriate hardness and improves the handling properties such as tensile strength in a semi-cured or uncured state. Furthermore, by including organic particles, the film exhibits good handling properties even when the film has a thickness of 100 μm or less or when a silicone resin with low hardness is used.

[0017] <Silicone resin> The silicone resin used in the present invention contains a silicone polymer (polyorganosiloxane) represented by the following formula (i). R n SiO (4-n) / 2 (i) Here, R is a substituted or unsubstituted monovalent hydrocarbon group, preferably a monovalent hydrocarbon group having 1 to 12 carbon atoms, more preferably 1 to 8 carbon atoms, n is a positive number of 1.95 to 2.05, and multiple R may be the same or different.

[0018] Examples of R include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and dodecyl groups; cycloalkyl groups such as cyclohexyl groups; alkenyl groups such as vinyl, allyl, butenyl, and hexenyl groups; and chloromethyl, trifluoropropyl, and cyanoethyl groups in which some or all of the hydrogen atoms bonded to the carbon atoms of these groups have been substituted with halogen atoms, cyano groups, or the like.

[0019] In addition, the polyorganosiloxane according to the present invention is preferably one in which the molecular chain end is blocked with a trimethylsilyl group, a dimethylvinyl group, a dimethylhydroxysilyl group, a trivinylsilyl group, or the like. Furthermore, the polyorganosiloxane preferably has at least two alkenyl groups in the molecule. Specifically, it is preferable that R has 0.001 mol% or more and 5 mol% or less, preferably 0.005 mol% or more and 3 mol% or less, more preferably 0.01 mol% or more and 1 mol% or less, particularly 0.02 mol% or more and 0.5 mol% or less of alkenyl groups, and it is particularly optimal to have a vinyl group. The polyorganosiloxane is basically linear, but may be partially branched. It may also be a mixture of two or more types with different molecular structures.

[0020] In the present invention, commercially available polyorganosiloxanes can be used. In addition, commercially available mixtures containing additives such as ceria-based fillers and silica-based fillers in addition to polyorganosiloxanes may be used. Specifically, products under the trade names "KE-5550-U", "KE-597-U", and "KE-594-U" manufactured by Shin-Etsu Chemical Co., Ltd. can also be used.

[0021] The resin composition is preferably a millable type containing polyorganosiloxane. The millable type resin composition is non-liquid (e.g., solid or paste-like) without self-flowability at room temperature (25°C) in an uncured state (e.g., uncured state before radiation exposure), but can be mixed uniformly by a kneader described later. The resin composition may contain a resin other than the silicone resin (polyorganosiloxane).

[0022] <Organic particles> The organic particles of the present invention are not particularly limited as long as they can produce the effects of the present invention, but are preferably at least one type selected from the group consisting of silicone rubber powder, silicone resin powder, silicone composite powder, crosslinked acrylic particles, and crosslinked urethane particles. (Silicone rubber powder) Silicone rubber powder refers to a fine powder mainly composed of a polyorganosiloxane cured product cured into a three-dimensional network. As the silicone rubber powder, for example, a fine powder having a highly polymerized three-dimensional structure in which linear dimethylpolysiloxane and / or methylphenylpolysiloxane with 0.05 mol % or more of vinyl groups are crosslinked with methylhydrogenpolysiloxane as a crosslinking agent, and modified products thereof can be preferably used. Specific examples of this silicone rubber powder include Shin-Etsu Chemical Co., Ltd.'s product names: KMP-402, KMP-597, and KMP-598.

[0023] (Silicone resin powder) Silicone resin powder refers to a fine powder whose main component is a polyorganosilsesquioxane cured product that has been cured into a three-dimensional network. Silicone resin powder is, for example, a powder in which the siloxane bond is represented by the general formula (RSiO 3 / 2 ) n [wherein R is a monovalent organic group, and n is an integer of 1000 or more], and modified products thereof can be suitably used. Here, examples of the organic group R in the above general formula include alkyl groups such as methyl, ethyl, propyl, isopropyl, and butyl groups, aryl groups such as phenyl and tolyl groups, alkenyl groups such as vinyl and allyl groups, 3,3,3-trifluoropropyl groups, γ-mercaptopropyl groups, γ-glycidoxypropyl groups, γ-methacryloxypropyl groups, and γ-aminopropyl groups.

[0024] Specific examples of silicone resin powders include Shin-Etsu Chemical Co., Ltd.'s product names: KMP-590, KMP-706, X-52-854, and X-52-1621, and Momentive Performance Materials, Inc.'s product names: XC99-A8808 and TOSPEAL120.

[0025] (Silicone composite powder) The silicone composite powder refers to a powder in which the surface of the silicone rubber powder is coated with the silicone resin. Specific examples of this silicone composite powder include the product names KMP-600, KMP-601, KMP-602, KMP-605, and X-52-7030 manufactured by Shin-Etsu Chemical Co., Ltd.

[0026] (Crosslinked acrylic particles) The crosslinked acrylic particles refer to fine powders mainly composed of acrylic polymers having a three-dimensional network structure. As the crosslinked acrylic particles, any of crosslinked acrylic particles made only of known acrylic polymers (including homopolymers and copolymers) including acrylic acid esters, methacrylic acid esters, etc., and crosslinked acrylic particles made of copolymers of known acrylic monomers including acrylic acid esters, methacrylic acid esters, etc. and other monomers (for example, known copolymerizable monomers such as styrene monomers) can be used. The crosslinking method can be selected from any known methods, including a method of increasing the degree of crosslinking by using a crosslinking monomer. The crosslinked acrylic particles may be used alone or in combination of two or more kinds.

[0027] Examples of commercially available crosslinked acrylic particles include MX-2000, MR-10HG, etc. (all manufactured by Soken Chemical Industry Co., Ltd.); GR-200, GR-400, GR-800, G-400, G-800, GS-310T, GS-350T, GS850TC (all manufactured by Negami Chemical Industry Co., Ltd.); FH-S005, FH-S008, FH-S010, FH-S015, FH-S020, FH-S050 (all manufactured by TOYOBO); MBX-5, MBX-8, MBX-12, MBX-20, MBX-30, MBX-40, MBX-50, MB20X-5, MB20X-30, MB30X-5, MB30X-8, MB30X-20 (all manufactured by Sekisui Chemical Co., Ltd.), but are not limited thereto, and can be appropriately selected in relation to the silicone resin.

[0028] (Crosslinked urethane particles) Crosslinked urethane particles are fine powders that are mainly composed of polyurethane with a three-dimensional mesh structure. Examples of crosslinked urethane particles include reaction products of polyisocyanate compounds and polyol compounds. Polyisocyanate compounds are organic compounds that have at least two isocyanate groups in one molecule. The crosslinked urethane particles can be obtained, for example, by reacting a di- or higher functional polyisocyanate compound with a polyol compound by a known method. The crosslinked urethane particles may be used alone or in combination of two or more kinds. As examples of crosslinked urethane particles, Daimic Beads (registered trademark) (Dainichi Seika Chemicals), Art Pearl (registered trademark) (Negami Kogyo Co., Ltd.), and the like, manufactured by Dainichi Seika Chemicals, can be suitably used.

[0029] The organic particles can be either amorphous or spherical, but fine spherical types are preferably used. When the organic particles are spherical, their average particle size is 0.1 μm to 100 μm, preferably 0.3 μm to 90 μm, more preferably 0.5 μm to 80 μm, and even more preferably 0.7 μm to 70 μm. When the average particle size is equal to or greater than the lower limit, the organic particles are less likely to aggregate with each other, and the strength of the film can be ensured. In addition, the viscosity of the silicone rubber containing the particles does not become too high, so that the moldability is not reduced. On the other hand, when the average particle size is equal to or less than the upper limit, the mechanical strength of the film is ensured, and the particles do not protrude from the film even when the film is thinned.

[0030] The specific gravity of the organic particles is preferably 0.4 to 1.8, more preferably 0.6 to 1.6, and even more preferably 0.8 to 1.5. When the specific gravity of the organic particles is equal to or higher than the lower limit, the organic particles can be suitably mixed with the silicone rubber. On the other hand, when the specific gravity is equal to or lower than the upper limit, the film can exhibit good vibration characteristics when used as a diaphragm.

[0031] The content of the organic particles in the resin composition is preferably 5 parts by mass or more and 200 parts by mass or less with respect to 100 parts by mass of the silicone resin. When it is 5 parts by mass or more, the handling property before crosslinking is good, and when it is 200 parts by mass or less, it is excellent in thermal formability and can maintain a low elastic modulus even after curing. From the above viewpoints, the content of the organic particles is more preferably 5 parts by mass or more and 150 parts by mass or less, and even more preferably 15 parts by mass or more and 120 parts by mass or less. From the viewpoint of maintaining the toughness of the film, the upper limit of the content of the organic particles is more preferably 90 parts by mass or less, even more preferably 60 parts by mass or less, and particularly preferably 30 parts by mass or less. The organic particles may be used alone or in combination of two or more kinds. When two or more kinds of organic particles are used, the above content refers to the total content of the organic particles.

[0032] (Filler) The resin composition may contain a filler. Suitable examples of the filler include silica, such as ceria (cerium oxide), fumed silica, and precipitated silica. By including a filler in the resin composition, the mechanical properties, such as the storage modulus and tensile elongation at break, of a film made of the resin composition can be easily adjusted to an appropriate range. In addition, the use of a filler makes it easy to adjust the viscosity and hardness of the resin composition, and also makes it easy to optimize the balance between the fluidity and secondary processability of the resin composition. Another advantage is that the hardness can be easily adjusted appropriately according to the design and acoustic characteristics of the acoustic component. In addition, the filler constitutes a part of the gel fraction in the measurement of the gel fraction, and the gel fraction of the present film increases by including a filler. Even if the gel fraction increases by including a filler, the hardness of the present film can be increased in the same way as in the case where the gel fraction increases by crosslinking.

[0033] The content of the filler in the resin composition is, for example, 10% by mass or more and 50% by mass or less, preferably 15% by mass or more and 40% by mass or less, more preferably 20% by mass or more and 35% by mass or less, based on the total amount of the resin composition. The average particle size of the filler is, for example, 0.01 μm or more and 20 μm or less, preferably 0.1 μm or more and 10 μm or less, more preferably 0.5 μm or more and 5 μm or less. The average particle size of the filler can be measured as the median size (D50) using a particle size distribution measuring device using a laser light diffraction method or the like.

[0034] In addition to the polyorganosiloxane, the resin composition may contain a crosslinking agent, and preferably contains an organic peroxide. By adding an organic peroxide, the film can be easily cured in the subsequent forming process. Considering the flexibility of the film, its conformity to the mold during molding, and its formability, it is preferable that the film has an appropriate degree of crosslinking. That is, in terms of hardness, it is preferable that the film is harder than an uncrosslinked film and softer than a cured film. For example, it is preferable that the film is in a semi-cured state so that the gel fraction is within a desired range. More specifically, the gel fraction is preferably in the range of 30 to 95%. When the gel fraction is in this range, the film is in a semi-cured state and has excellent handleability. From the above viewpoints, the gel fraction is more preferably in the range of 40 to 90%, and further preferably in the range of 50 to 80%.

[0035] Examples of organic peroxides include alkyl peroxides such as di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane; aralkyl peroxides such as 2,4-dicumyl peroxide; and acyl peroxides such as benzoyl peroxide, di(4-methylbenzoyl)peroxide, and di(2-methylbenzoyl)peroxide. From the viewpoints of crosslinking rate and safety, alkyl peroxides, in particular, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, are preferred. In addition, when the film is exposed to air during heating, acyl peroxides, particularly di(4-methylbenzoyl) peroxide, which are less susceptible to curing inhibition by oxygen, may be used.

[0036] The amount of organic peroxide in the resin composition is preferably 0.01% by mass or more and 10% by mass or less, more preferably 0.03% by mass or more and 5% by mass or less, even more preferably 0.05% by mass or more and 4% by mass or less, particularly preferably 0.1% by mass or more and 3% by mass or less, and particularly preferably 0.3% by mass or more and 2% by mass or less, based on the total amount of the resin composition. If the amount of organic peroxide is within this range, a composition having a sufficient curing speed tends to be obtained safely.

[0037] The present resin composition may contain various additives such as heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, antibacterial and antifungal agents, antistatic agents, lubricants, pigments, dyes, flame retardants, and impact resistance improvers, provided that the effects of the composition are not impaired.

[0038] <Viscoelastic properties (storage modulus)> The present film preferably exhibits the following viscoelastic properties (a) to (c) upon thermal curing. (a) Storage modulus E' at a measurement temperature of 25°C and a frequency of 10 Hz 25 is between 0.1MPa and 5MPa. (b) Storage modulus E' at a measurement temperature of 200°C and a frequency of 10 Hz 200 is between 0.1MPa and 5MPa. (c) Storage modulus E' 25 Storage modulus E' 200 The ratio (E' 200 / E' 25 ) is between 0.2 and 1.5.

[0039] (a) Storage modulus E' at a measurement temperature of 25°C and a frequency of 10 Hz 25 When E' is 0.1 MPa or more, the hardness after curing is constant, and the handling property after curing is good. 25 When the film is used as a diaphragm, the diaphragm tends to have excellent acoustic characteristics such as sound quality and reproducibility. 25 is more preferably 1 MPa or more and 5 MPa or less, further preferably 1.5 MPa or more and 5 MPa or less, and further preferably 2 MPa or more and 5 MPa or less.

[0040] Also, (b) Storage modulus E' at a measurement temperature of 200°C and a frequency of 10 Hz 200 When the elastic modulus E' is 0.1 MPa or more and 5 MPa or less, the heat resistance is good, and it is expected that excellent acoustic properties can be obtained even in a high temperature environment. 200 is more preferably 0.2 MPa or more and 5 MPa or less, even more preferably 0.5 MPa or more and 4 MPa or less, even more preferably 1 MPa or more and 4 MPa or less, and particularly preferably 1.5 MPa or more and 3.5 MPa or less.

[0041] Also, (c) the ratio of storage moduli (E' 200 / E' 25By setting the value of 0.2 to 1.5, the change in elastic modulus due to temperature change is small, and heat resistance tends to be good. In addition, since the change in elastic modulus when heated is small, sound quality is less likely to deteriorate in high-temperature environments, and it becomes easier to maintain excellent sound reproduction from low to high temperature ranges. From the above viewpoint, the above ratio (E' 200 / E' 25 ) is more preferably 0.25 or more and 1 or less, further preferably 0.3 or more and 0.9 or less, and particularly preferably 0.35 or more and 0.8 or less. The storage modulus was measured by the method described in the Examples section after hardening the composition using a simple press molding method in which the composition was heated at 200° C. for 2 minutes under a pressure of 0.2 MPa and then cured.

[0042] The present film is a film having a curing property, and the type of curing may be any of photocuring, moisture curing, and heat curing, but it is preferable that the film has a thermosetting property. Since the present film has a thermosetting property, it can be cured when it is heated to be molded, so that the moldability is further improved. In addition, since the present film has a curing property, its gel fraction increases by performing a curing process such as heating.

[0043] The present film preferably has a crosslinked structure. By having a suitable crosslinked structure, it becomes easier to obtain a film having suitable viscoelastic properties when crosslinked and cured. In addition, it becomes easier to improve the shape retention before curing (i.e., before molding). The present film may have a surface portion crosslinked and an inside portion uncured, but considering the flexibility of the film, its conformity to a mold during molding, and its shaping property, it is preferable that the film as a whole has an appropriate degree of crosslinking. That is, the hardness of the entire film is preferably a film that is harder than an uncrosslinked film and softer than a film cured by thermal shaping, that is, a so-called semi-cured film. In the present invention, the presence or absence of a crosslinked structure can be identified by the presence of a trace amount of unreacted crosslinking agent contained in the film in the case of a condensation type and the presence of a crosslinking agent after reaction (decomposition), and by the presence of a vinyl group involved in the crosslinking reaction in the case of an addition type.

[0044] The thickness of the present film is preferably in the range of 1 to 800 μm, more preferably in the range of 20 to 300 μm, and further preferably in the range of 50 to 200 μm. If the thickness of the present film is within this range, a film with little thickness variation during the film production process can be produced, and a molded product with a thickness suitable for, for example, a diaphragm can be produced.

[0045] <Tensile elongation at break> The tensile elongation at break of the film after curing is preferably 130% or more, more preferably 150% or more, and even more preferably 170% or more. If the tensile elongation at break is within this range, the toughness of the film is high, so that breakage due to long-term vibration is unlikely to occur, and durability tends to be excellent when used in acoustic components such as diaphragms. The higher the tensile elongation at break, the better, and although there is no particular upper limit, it is usually 1500% or less. The tensile elongation at break was measured by measuring the elongation at break of the cured film in TD (the direction perpendicular to the resin flow direction) at a tensile speed of 200 mm / min at 23°C according to a method in accordance with JIS K7161:2014.

[0046] <Silicone film with release film> The present film may be provided with a release film and used as a silicone film with a release film. The silicone film with a release film includes the present film described above and a release film provided on at least one side of the present film. In the case of a silicone film with a release film, it is preferable that a release film is provided on both sides of the present film.

[0047] The release film may be a resin film, or a resin film having a release layer on at least one side of which a release treatment has been performed. When the release film has a release layer, it is preferable that the release layer is laminated on the present film so that the release layer is in contact with the present film. Examples of resins used in the release film include polyolefin resins such as polypropylene, acrylic resins, polystyrene resins, polyacetal resins, polyamide resins, polyester resins, polycarbonate resins, ABS resins, polyether ether ketone resins, etc. Among these, polyester resins are preferred, and polyethylene terephthalate resins are particularly preferred. The thickness of the release film is not particularly limited, but is preferably from 5 μm to 150 μm, more preferably from 7 μm to 120 μm, further preferably from 10 μm to 100 μm, and particularly preferably from 10 μm to 80 μm.

[0048] The present film is protected by the release film attached thereto. This prevents the present film from being scratched during transportation, etc. The release film may be the release film laminated during the production of the present film, or may be laminated separately to the produced present film. The present film is molded, for example, by a mold-forming method as described below, and the release film is preferably peeled off from the present film during molding and then set in a mold such as a metal die. At that time, the present film can be peeled off from the release film without being torn.

[0049] <Manufacturing method of this film> The present film can be molded by a general molding method, for example, extrusion molding, etc. A resin composition for obtaining the film may be obtained by kneading or the like as described below, and then molded by extrusion molding or the like.

[0050] Each resin composition is not particularly limited, but can be obtained, for example, by kneading the materials constituting the resin composition. As a kneader used for kneading, a known kneader such as an extruder such as a single screw or twin screw extruder, a calendar roll such as a two-roller or three-roller, a roll mill, a plastomill, a Banbury mixer, a kneader, or a planetary mixer can be used. The kneading temperature is adjusted as appropriate depending on the type and mixing ratio of the resins, and the presence and type of additives. In order to suppress crosslinking (curing) while appropriately lowering the viscosity of the resin to facilitate kneading, the kneading temperature is preferably from 20°C to 150°C, more preferably from 30°C to 140°C, even more preferably from 40°C to 130°C, particularly preferably from 50°C to 120°C, and especially preferably from 60°C to 110°C. The kneading time may be long enough to uniformly mix the materials constituting the resin composition, and may be, for example, several minutes to several hours, and preferably 5 minutes to 1 hour.

[0051] The present film can be partially cured by heating, irradiating with light, adding moisture, or a combination of these to the film obtained as described above. In the present invention, it is preferable to partially cure the film by irradiation with radiation, since the film properties can be easily adjusted and mass production can be performed at a high speed. The radiation is not particularly limited as long as it cures the resin composition according to the present invention, and for example, ionizing radiation such as ultraviolet light, electron beam, etc. can be suitably used. The irradiation dose, irradiation time, etc. can also be appropriately determined within a range in which the resin composition can be cured and so as to achieve a desired degree of cure.

[0052] [Molded products] The film can be molded into a molded product by molding it in a mold such as a metal mold and curing it, and typically it is molded into various molded products by molding it in a mold. Curing can be performed according to the properties of the film, and can be performed by heating, light irradiation, moisture addition, or a combination of these, but is preferably performed by heating. The film is useful as a film for diaphragms, and molded products made of the film are particularly useful as acoustic components such as diaphragms.

[0053] The molded article of the present invention is made of a resin composition containing a silicone resin and organic particles, and has the following viscoelastic properties (a) to (c). (a) Storage modulus E' at a measurement temperature of 25°C and a frequency of 10 Hz 25 is between 0.1MPa and 5MPa. (b) Storage modulus E' at a measurement temperature of 200°C and a frequency of 10 Hz 200 is between 0.1MPa and 5MPa. (c) Storage modulus E' 25 Storage modulus E' 200 The ratio (E' 200 / E' 25 ) is between 0.2 and 1.5. Furthermore, the above requirements (a) to (c) are similar to those for the viscoelastic properties of the cured product obtained by thermally curing the film of the present invention, and the preferred ranges are also similar. The type and content of the organic particles in the molded article are also the same as those described for the film of the present invention, and the preferred ranges are also the same. The thickness of the molded article of the present invention is the same as that of the film of the present invention, and the preferred range is also the same.

[0054] In the present invention, the gel fraction of the molded product obtained from the film may be 80% or more. When the gel fraction is 80% or more, it is easy to obtain a molded product having a storage modulus and mechanical strength suitable for an acoustic member. The gel fraction of the molded product is more preferably 85% or more, and even more preferably 90% or more. The gel fraction of the molded product is not particularly limited in terms of the upper limit, and may be 100% or less, but generally may be lower than 100%, for example, 99% or less. The gel fraction of the molded product is the gel fraction of the entire molded product, and may be measured by sampling uniformly in the thickness direction of the molded product. Details of the method for measuring the gel fraction are as described in the examples.

[0055] <Method of manufacturing molded products> A molded article can be obtained using the present film. A method for producing a molded article using the present film will be described below. When obtaining a molded article from the present film, it is preferable to carry out at least the following steps 1 and 2. Step 1: Heating the film, forming it into a mold, and curing the film Step 2: The molded and cured film (i.e., the molded product) is peeled off from the mold.

[0056] Each step will now be described in more detail. (Process 1) In step 1, the film is heated and molded in a mold, and the film is cured to form a molded article. The molded article is preferably shaped in a mold, and is thereby formed into a desired shape. The molding in step 1 is not particularly limited, and may be performed by any molding method such as vacuum molding, pressure molding, and press molding, among which press molding is preferred because it is easier to mold.

[0057] A mold may be prepared according to the molding method, and the mold may have projections and recesses according to the shape of the molded product to be manufactured. A metal mold (metal die) is typically used as the mold, but a resin mold may also be used. For example, as described below, if the molded product (diaphragm) has at least one of a dome shape and a cone shape, the mold may have projections and recesses corresponding to the dome shape or the cone shape. In addition, if the molded product (diaphragm) has a tangential edge on the surface, the mold may have projections and recesses corresponding to the tangential edge.

[0058] As described above, a release film may be attached to this film, and it is preferable that the release film is peeled off as described above before the film is set in the mold.

[0059] In step 1, the heated film may be shaped by a mold, for example, the film placed on the mold may be shaped by the mold while being heated, or the film may be preheated and placed on the mold and then shaped by the mold, or a combination of these may be used. The film may be heated by any method, for example, when the film placed on the mold is heated, the mold may be heated and the film may be heated by heat transfer, or the film may be heated by another method.

[0060] The heating temperature during shaping or curing is preferably from 180° C. to 260° C., more preferably from 190° C. to 250° C., and even more preferably from 200° C. to 240° C. If the temperature during shaping or curing is within this range, the present film tends to be able to cure at a sufficient speed without being melted or deformed by heat.

[0061] The shaping time is preferably 1 second to 5 minutes, more preferably 5 seconds to 4 minutes, even more preferably 10 seconds to 3 minutes, and particularly preferably 20 seconds to 2 minutes. If the heat treatment time during shaping is within this range, it tends to be easy to sufficiently harden the composition while maintaining productivity. The film is preferably cured while being shaped, but may be cured after shaping without any particular limitation. The shaping time refers to the time during which the film is shaped or cured in the mold, and does not include the time required for moving the mold before and after shaping, or the time required for releasing the laminate from the mold.

[0062] (Process 2) In step 2, the film formed and cured in step 1 is peeled off from the mold to obtain a molded article. In the present invention, the gel fraction of the film is less than a certain value, so that the film has high formability and high conformability to the mold. Therefore, the molded article can be produced with high molding accuracy. In addition, since the film has specific viscoelastic properties, it has high shape retention and good handling properties. Furthermore, it can be peeled off from the release film without breaking, and can be easily set in a mold while maintaining the shape of the film. Furthermore, since the release film is not laminated, the process of peeling the release film from the molded product can be omitted, making mass production easier.

[0063] [Application] The silicone film of the present invention can be suitably used for acoustic components. Specifically, it can be suitably used as a film for acoustic components, particularly as a film for diaphragms. The acoustic components of the present invention, such as diaphragms, are preferably made by curing the present film, and specifically, may be made of the above-mentioned molded products. The acoustic components are more preferably diaphragms, specifically speaker diaphragms, and can be suitably used as microspeaker diaphragms for mobile phones and the like.

[0064] This film can be formed into various acoustic components such as diaphragms by appropriate molding. The acoustic member may have, for example, at least a portion thereof in a dome shape or a cone shape. The acoustic member may also have a tangential edge on the surface. When the acoustic member has a dome or cone shape or a tangential edge, the acoustic member is preferably used as a diaphragm, more preferably as a speaker diaphragm.

[0065] (diaphragm) To explain the diaphragm in more detail, the shape of the diaphragm is not particularly limited and can be any shape, such as a circle, an ellipse, or an oval. The diaphragm generally has a body that vibrates in response to an electric signal or the like, and an edge surrounding the periphery of the body. The body of the diaphragm is usually supported by the edge. The shape of the diaphragm may be a dome shape or a cone shape as described above, a shape that combines these shapes, or any other shape used for a diaphragm.

[0066] The film may form at least a portion of the acoustic member, for example the body or edge of the diaphragm may be formed by the film and the edge or body of the diaphragm may be formed by another member, or both the body and edge may be integrally formed by the film, or the entire diaphragm may be formed by the film.

[0067] Fig. 1 is a diagram showing the structure of a diaphragm 1 according to one embodiment of the present invention, and is a cross-sectional view of the diaphragm 1, which is circular in plan view, cut along a plane passing through the center line of the circle. The diaphragm 1 is a diaphragm for a micro speaker. As shown in Fig. 1, the diaphragm 1 has a dome portion (body) 1a at the center, a recessed portion 1b to be attached to a voice coil 2, a peripheral portion (edge) 1c, and an external attachment portion 1d on the outer periphery thereof to be attached to a frame or the like.

[0068] FIG. 2 is a diagram showing the structure of a diaphragm 11 according to another embodiment of the present invention, and is a cross-sectional view of the circular diaphragm 11 cut along a plane passing through the center line of the circle in a plan view. The diaphragm 11 is a diaphragm for a micro speaker. As shown in FIG. 2, the diaphragm 11 has a dome-shaped dome part (body) 11a at the center, a recessed fitting part 11b attached to the voice coil 2, a cone part 11j processed into a cone shape, and a peripheral part (edge) 11c. As shown in the diaphragm 11 as an example, the diaphragm may have a part processed into a dome shape and the other part processed into a cone shape. Note that the peripheral part 11c of the diaphragm 11 may be directly attached to a frame or the like, or may be attached to a frame or the like via another member.

[0069] As described above, a tangential edge may be provided on the surface of the diaphragm. The tangential edge may be, for example, a groove having a V-shaped cross section. FIG. 3 shows a plan view of a diaphragm 21 according to another embodiment of the present invention. The diaphragm 21 has a tangential edge portion 21g having a plurality of tangential edges 21e provided on the outer periphery of a circular dome portion (body) 21a, and a tangential edge portion 21h having a plurality of tangential edges 21f arranged on the outer periphery of the tangential edge portion 21g. Note that, although FIG. 3 shows an example in which two tangential edge portions are provided along the radial direction, the number of tangential edge portions may be only one or three or more may be provided along the radial direction.

[0070] As described above, the diaphragm is preferably a speaker diaphragm, particularly a micro speaker diaphragm. From the viewpoint of suitable use as a micro speaker diaphragm, the size of the diaphragm is a maximum diameter of 25 mm or less, preferably 20 mm or less, and a maximum diameter of 5 mm or more is preferably used. The maximum diameter refers to the diameter when the diaphragm is circular, and the major axis when the diaphragm is elliptical or oval.

[0071] The diaphragm may be formed from the present film alone, or may be formed from a composite material of the present film and another material. For example, either the edge or the body may be formed from another material as described above.

[0072] Furthermore, in order to improve the secondary processing suitability and dust resistance of the diaphragm, or to adjust the acoustic characteristics and improve the design, etc., the surface of the diaphragm may be appropriately treated by coating an antistatic agent, depositing a metal, sputtering, coloring (black, white, etc.), etc. Furthermore, lamination with a metal such as aluminum, or compounding with a nonwoven fabric, etc. may be appropriately performed.

[0073] (acoustic transducer) The acoustic transducer of the present invention is an acoustic transducer having the above-mentioned acoustic member, preferably a diaphragm. The acoustic transducer is typically an electroacoustic transducer, and examples thereof include a speaker, a receiver, a microphone, and an earphone. Of these, the acoustic transducer is preferably a speaker, and a micro-speaker of a mobile phone or the like is suitable. EXAMPLES

[0074] The present invention will be described in detail below using examples, but the present invention is not limited to these examples.

[0075] (Evaluation method) 1.Storage modulus E' A test piece of 4 mm×8 cm was cut out from the press-molded film obtained in each Example and Comparative Example to obtain a measurement sample. The storage modulus and tan δ of the measurement sample were measured using a viscoelasticity spectrometer "DVA-200 (manufactured by IT Measurement & Control Co., Ltd.)" in accordance with JIS K7244-4:1999, with the measurement mode set to tension, the frequency set to 10 Hz, the strain set to 0.1%, the temperature range set to -100 to 300°C, and the heating rate set to 3°C / min.

[0076] 2. Gel fraction The gel fraction of the film before and after press molding was measured by the following method. As is clear from the following measurement method, the gel fraction is calculated by including not only the crosslinking component contained in the film but also insoluble components other than the crosslinking component such as a filler as the gel fraction. (2-1) Approximately 100 mg of sample was cut out uniformly in parallel to the thickness direction of the film, and the mass (a) of the sample was measured. (2-2) The collected sample was immersed in chloroform at 23°C for 24 hours. (2-3) The solid content in chloroform was taken out and dried in vacuum at 50° C. for 7 hours. (2-4) The mass (b) of the solid content after drying was measured. (2-5) The gel fraction was calculated using the masses (a) and (b) according to the following formula (vi).

[0077]

number

[0078] 3. Handling The handling properties of the pre-cured films obtained in each Example and Comparative Example were evaluated. When the film was peeled off from the release film and used for various evaluations and measurements, the film was rated as "good" if it could be easily handled because its shape was maintained, and "poor" if it could not maintain its shape and the film itself became tangled or torn during the handling process.

[0079] (4) Formability A test piece of about 7 cm x 10 cm was cut out from the film obtained in each Example and Comparative Example to be used as an evaluation sample. The evaluation sample was sandwiched between a dome-shaped diaphragm mold with a tangential edge that had been preheated to 230°C and pressed at a pressure of 0.1 MPa. The sample was held in this pressurized state for 20 seconds and then removed from the mold. After removal, the samples were visually inspected; those that had the same irregularities as those in the mold were rated as "O", and those that only had irregularities smaller than those in the mold or no irregularities at all were rated as "X".

[0080] (Resin composition raw material) A-1: Silicone rubber (mixture of organopolysiloxane and silica, product name "XIAMETERTM SE1185U", manufactured by Dow Toray Co., Ltd., silica content 30% or more but less than 40%, specific gravity 1.15) B-1: Organic peroxide compound silicone rubber (organic peroxide), silicone rubber containing approximately 40% 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane (product name "C-8B", manufactured by Shin-Etsu Chemical Co., Ltd.)

[0081] C-1: Organic particles, silicone rubber powder (product name "KMP-598", manufactured by Shin-Etsu Chemical Co., Ltd., average particle size approximately 13 μm, particle size distribution 2 to 30 μm, true specific gravity 0.97) C-2: Organic particles, silicone resin powder (product name "KMP-706", manufactured by Shin-Etsu Chemical Co., Ltd., average particle size approximately 2 μm, particle size distribution 1 to 4 μm, true specific gravity 1.3) C-3: Organic particles, silicone resin powder (product name "X-52-1621", manufactured by Shin-Etsu Chemical Co., Ltd., average particle size approximately 5 μm, particle size distribution 1 to 8 μm, true specific gravity 1.3) C-4: Organic particles, silicone composite powder (product name "KMP-600", manufactured by Shin-Etsu Chemical Co., Ltd., average particle size approximately 5 μm, particle size distribution 1 to 15 μm, true specific gravity 0.99) C-5: Organic particles, silicone composite powder (product name "KMP-601", manufactured by Shin-Etsu Chemical Co., Ltd., average particle size approximately 12 μm, particle size distribution 2 to 25 μm, true specific gravity 0.98) C-6: Organic particles, crosslinked acrylic fine particles (product name "ART PEARL SE-015TY", manufactured by Negami Kogyo Co., Ltd., average particle size approximately 15 μm, true specific gravity 1.3) C-7: Organic particles, crosslinked urethane fine particles (product name "ART PEARL C-400T", manufactured by Negami Kogyo Co., Ltd., average particle size approximately 15 μm, true specific gravity 1.16) D-1: Inorganic particles, silica (product name "Sunsphere H-51", manufactured by AGC Si-Tech Co., Ltd., average particle size about 5 μm, specific gravity about 2.0 to 2.3)

[0082] Example 1 As raw materials, 100 parts by mass of silicone rubber (A-1), 1 part by mass of organic peroxide (B-1), and 20 parts by mass of organic particles (C-1) were kneaded using a mixer at a temperature of 90°C for 5 minutes to obtain a millable resin composition (1). A PET film (1) with a surface roughness (Ra) of 0.98 μm on the matte side was prepared as a release film, and was fed along two calendar rolls with a diameter of 100 mm so that the matte side was on the inside. The resin composition (1) was placed between the release films, and a bank was formed on the roll at a roll temperature of 80°C, and the thickness of the resin composition (1) was adjusted to 100 μm to obtain a silicone film with a release film. The obtained silicone film was irradiated with radiation. After irradiation with radiation, the release films on both sides were peeled off to obtain a silicone film sample. The obtained sample was cured by a simple method of press molding from two flat plates at a pressure of 0.2 MPa while heating at 200°C for 2 minutes, assuming the production of a molded product by extrusion molding. The gel fraction and storage modulus of this sample before press molding were measured, and the handling property and formability were evaluated. In addition, the storage modulus of this sample after press molding was measured. The results are shown in Table 1.

[0083] Examples 2 to 9, Comparative Examples 1 and 2 A sample was obtained in the same manner as in Example 1, except that the organic particles and inorganic particles shown in Table 1 were used in the proportions shown in Table 1. The gel fraction and storage modulus of this sample before press molding were measured, and the handling property and formability were evaluated. In addition, the storage modulus of this sample after press molding was measured. The results are shown in Table 1.

[0084] [Table 1]

[0085] As shown in Table 1, the present films of Examples 1 to 9, in which 20 parts by mass or more of organic particles were added, had a storage modulus E' at 25°C of the sheet before press molding even when the gel fraction was 90% or less. 25The storage modulus E' was improved to 1.5 MPa or more, showing good handling properties. 25 Since the elastic modulus remains low at 5 MPa or less, it is expected to provide good sound quality when used as a diaphragm. Among organic particles, C-1 and C-5 with an average particle size of 10 μm or more are used, which results in a smaller storage modulus E' after press molding. 25 This is considered to be more preferable since it shows the following. On the other hand, in the film of Comparative Example 1, the storage modulus E' before press molding 25 The storage modulus E' before press molding was 1.4 MPa, which was small, and the film was difficult to handle, as it became tangled when peeling it off from the release film or when placing it in a press mold. In addition, in the film of Comparative Example 2, the addition of inorganic silica particles reduced the storage modulus E' before press molding. 25 The storage modulus E' after press molding was significantly improved, and handling was improved. 25 This significantly increases the pressure to 8.6 MPa, raising concerns that it may not be possible to achieve suitable sound quality when used as a diaphragm. [Industrial Applicability]

[0086] The film of the present invention has excellent heat formability while maintaining good handleability before crosslinking, and even if the gel fraction is 95% or less, the storage modulus E' at 25°C of the sheet before press molding is 25 It also has low elasticity even after press molding, and is expected to produce good sound quality when used as a diaphragm, making it a technology of great industrial value. [Explanation of symbols]

[0087] 1, 11, 21 diaphragm 1a, 11a, 21a Dome section (body) 1b, 11b recessed part 1c, 11c Edge 1d External attachment part 11j Cone section 21e, 21f Tangential Edge 21g, 21h Tangential edge 2 Voice coil

Claims

1. A film comprising a resin composition containing a silicone resin and organic particles.

2. The film according to claim 1 , wherein the content of the organic particles is 5 parts by mass or more and 200 parts by mass or less with respect to 100 parts by mass of the silicone resin.

3. 2. The film according to claim 1, wherein the organic particles are at least one selected from the group consisting of silicone rubber powder, silicone resin powder, silicone composite powder, crosslinked acrylic particles, and crosslinked urethane particles.

4. The film of claim 1 having thermosetting properties.

5. The film of claim 1, having a gel fraction of 30 to 95%.

6. The film according to claim 4, which has the following viscoelastic properties (a) to (c) upon thermal curing: (a) Storage modulus E′ at a measurement temperature of 25° C. and a frequency of 10 Hz 25 is 0.1 MPa or more and 5 MPa or less. (b) Storage modulus E′ at a measurement temperature of 200° C. and a frequency of 10 Hz 200 is 0.1 MPa or more and 5 MPa or less. (c) Storage modulus E' 25 Storage modulus E' 200 The ratio of (E' 200 / E' 25 ) is greater than or equal to 0.2 and less than or equal to 1.

5.

7. The film of claim 1 for use in an acoustic component.

8. A film with a release film, comprising the film according to any one of claims 1 to 7 and a release film on at least one side of the film.

9. A molded article comprising a resin composition containing a silicone resin and organic particles, and having the following viscoelastic properties (a) to (c): (a) Storage modulus E′ at a measurement temperature of 25° C. and a frequency of 10 Hz 25 is 0.1 MPa or more and 5 MPa or less. (b) Storage modulus E′ at a measurement temperature of 200° C. and a frequency of 10 Hz 200 is 0.1 MPa or more and 5 MPa or less. (c) Storage modulus E' 25 Storage modulus E' 200 The ratio of (E' 200 / E' 25 ) is greater than or equal to 0.2 and less than or equal to 1.

5.

10. The molded article according to claim 9 , wherein the content of the organic particles is 5 parts by mass or more and 200 parts by mass or less with respect to 100 parts by mass of the silicone resin.

11. 10. The molded article according to claim 9, wherein the organic particles are at least one selected from the group consisting of silicone rubber powder, silicone resin powder, silicone composite powder, crosslinked acrylic particles, and crosslinked urethane particles.

12. The molded article according to claim 9, which is for an acoustic component.

13. An acoustic transducer comprising the molded product according to claim 9.

Citation Information

Patent Citations

  • Sheet for vibration plate and vibration plate manufacturing method using the same

    JP2018152817A

  • Photocurable silicone gel composition

    WO2014061390A1